Kebolehan Wanita Berkarir Dalam Pandangan Al-Quran - Masripah Masripah; Yufi Mohammad Nasrullah; Nurul Fatonah (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
The Permissibility of Women's Career in the View of the Al-QuranThis study discusses career women in the view of the Koran. This study focuses its study on the description of the conception of career women, its relation in the view of the Qur'an. The source of data in this study was obtained from the holy book of the Qur'an and several other sources in the form of supporting and comparison references in accordance with the research theme. This research is library research using a qualitative approach, which is trying to describe a variable, symptom or situation. The results of this paper show that Islam is a religion that is very flexible and understands women, where a career for women is okay as long as it does not go out of the corridor of Islamic teachings, namely avoiding things that are jahiliyyah such as mixing with men. foreigners (ikhtilath), showing off their genitals (tabarruj), softening the voice with the intention of attracting men's hearts, and being alone (khalwat) with non-muhrim which can cause slander. Then in its implementation, it must obtain the permission of parents (if not married) or husband, and maintain their views (ghadhdh al-bashar) and for reasons that do not conflict with Islamic teachings